Molluscicidal Activity of Legumes, Yellow Flame (Peltophorum Pterocarpum) and Raintree (Samanea Saman) on Freshwater Snails; Indoplanorbis Exustus (Pulmonata: Planorbidae) and Radix Quadrasi (Pulmonata: Lymnaeidae) - Bilal, Amal Ibrahim Khalifa (2002)
Acute toxicity by static bioassay of ground dried leaves (medium age) of leguminoses, yellow flame (Peltophorum pterocarpum) and rain tree (Samanea saman), in the form of ground powder solution, crude water and methanol extract was determined against target freshwater snails, Indoplanorbis exustus (Planorbidae) and Radix quadrasi (Lymnaeidae), and also on non-target species, red tilapia, Oreochromis niloticus, and shrimp, Macrobrachium lanchesteri using static bioassay technique. The field-collected snails were examined for the infection of trematode larvae. 1. exustus was found to be the host to the two types of trematodes larvae (cercaria), namely furcocercous cercariae, bifurcated cercaria (schistosoma) and gymnocephalus cercariae, non-bifurcated tail cercaria (fasciola), whereas, R. quadrasi was found to be the host to the various types of gymnocephalus cercariae. The toxicity results indicated that molluscicidal and piscicidal activity is not limited to any particular plant species and that the dried ground leaves powder, crude water, and methanol extract; of P. plerocarpum and S. saman are toxic to the target and non-target species. However, toxicity of the crude methanol extracts of these plants exhibited the highest potency as compared to the crude water extract and dried ground leaves. The 24 h LC50 of crude water and methanol extract of P. pterocarpum against the target species was found to be within the standard range of World Health Organization (l00 mgtl) of being molluscicidally active. Based on the 24h LC50 values, the results indicated that the potency of P. pterocarpum treatments on the target snail species follow this trend; crude methanol extract (50.7- 55.6 mgtl) was the most potent, followed by crude water extract (64.9-72.7 mgtl) and the dried, ground powder (338.2-390.4 mgtl). Comparison test between 1. exustus and R. quadrasi showed that R. quadrasi was more sensitivity to crude methanol extract of P. pterocarpum than the S. saman, with 24h LCso value of 50.7 mg/l and 1 08 mgtl, respectively. Test carried out on the non-target species, shrimp, M lanchesteri was observed to be virtually absence of the toxic effect when exposed at the concentrations that kill 50% of the target snail species. But, red tilapia, 0. niloticus was more susceptible and LCso was obtained at the lower concentrations than the concentration that caused 50% mortality of the target snail species. The relationship of 24h LCso values to the different snail shell length of laboratory breed R. quadrasi and 1. exustus was also investigated using crude methanol extract of P. pterocarpum. Results indicated that the relationship between different shell length of R. quadrasi and 24h LCso was a positively correlated with r = 0.98, but the relationship was polynomial (quadratic) with the equation line of Y= 0.63 x2 -8.5x +42.7. In the case of 1. exuslus there was positive correlation between its sensitivity and its sizes, and relationship was linear with regression line of Y=2.77 x +8.3 and r of 0.96.